A LC/QTOF–MS/MS Application to Investigate Chemical Compositions in a Fraction with Protein Tyrosine Phosphatase 1B Inhibitory Activity from Rosa Rugosa Flowers. Issue 6 (28th June 2013) - Gu, Dongyu; Yang, Yi; Bakri, Mahinur; Chen, Qibin; Xin, Xuelei; Aisa, Haji Akber
ABSTRACT: Introduction: Rosa rugosa flowers used as herbal medicine possess many activities. A fraction extracted by ethyl acetate exhibited strong inhibitive activity against protein tyrosine phosphatase 1B (PTP1B) in vitro . Objective: Establish an efficient method of LC coupled to quadrupole time‐of‐flight (QTOF) with tandem MS/MS to investigate the compositions in the active fraction. Methods: Chemical compositions were separated and investigated by LC/QTOF–MS/MS in negative electrospray ionisation (ESI) mode at different collision energy (CE) values. The maximal structural information was obtained for the identification of components. Results: A total of 75 compounds including tannins, their related compounds and flavonoids were identified or partially characterised according to accurate mass and the characteristic fragments at low and high CE. Meanwhile, the fragmentation pathways of gallotannins and ellagitannins (hexahydroxydiphenoyl group and lactonised valoneoyl group) were studied and proposed and were used to trace tannins in crude extracts. Conclusion: The results suggest that this fraction is a source of PTP1B inhibitory activity with a potential for treating diabetes. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : As a traditional herbal medicine, Rosa rugosa flowers possess many activities. In this study, a LC‐MS method was established for investigation of chemical compositions in a fraction with the PTP 1B inhibitory activity from Rosa rugosa. And 75 chemical compositions in this fraction were identified or tentatively characterized. The fragmentation pathways of gallotannins and ellagitannins were proposed. Knowing the phytochemical profiles of PTP 1B inhibitory activity fraction of this plant gives insights to its potential application to promote health.